The new urban wastewater treatment directive from the perspective of the receiving rivers’ quality - Máté Krisztián Kardos; Miklós Patziger; Zsolt Jolánkai; Adrienne Clement (Environmental Sciences Europe)
Abstract Background The European Union is reformulating key water management directives: the Urban Wastewater Treatment Directive (UWWTD) and the Water Framework Directive. The UWWTD update mandates extended removal of nutrients and stricter limits on micropollutants, primarily at wastewater treatment plants with a constructed capacity above 10 000 population equivalents. The revised Environmental Quality Standards Directive expands the list of regulated pollutants and lowers permissible concentrations for priority substances, including pharmaceuticals. The present study, applied for the Central-European country Hungary as a pilot, examines the impact of the UWWTD recast on receiving water quality. Employing a mixing model to assess the impact of municipal wastewater treatment plant emissions on regional waters, the research aims to optimize resource allocation for plant improvements and enhance risk area designation methods. Results Based on the evaluation of 886 river water bodies, it was found that wastewater plant effluents explain most of the current river impairment. Stricter nitrogen and phosphorus standards foreseen in the UWWTD recast will reduce the fraction of water bodies failing to achieve good ecological status by ~ 10%. The introduction of the new environmental quality standards for pharmaceuticals, in particular clarithromycin and diclofenac, will reveal that almost half of the river water bodies fail to achieve the good chemical status. Even after the implementation of micropollutant removal at the largest plants, as required by the recast, this number will not improve substantially. Conclusions The UWWTD recast’s stricter effluent standards for nutrients are projected to remarkably reduce the number of water bodies failing to achieve good ecological status, particularly in lowland rivers. However, the chemical status for pharmaceuticals like diclofenac remains concerning, with more than 40% of streams expected to fail under the revised limits. To overcome this, it is suggested to revise how the implementation of micropollutant removal at plants is prioritized. In addition to plant constructed capacity, the receiving water’s dilution capacity is to be considered at the prioritization and the designation of areas at risk.